Analysis of Business Financing for Small Scale Fishermen by Islamic Financial Institutions (Study in Untia Village, Makassar) - Warda Warda (Institute of Research and Community Service, University of Brawijaya)
The problem of financing for small scale fisherman has become a phenomenon that until today has not been overcome, even though it is seen from the potential of fisheries and Indonesian sea which is quite extensive if managed properly it will provide a large contribution to the country. This study aims to (1) understand the phenomena of financing small scale fisherman in Untia village and identify the problems being experienced by small scale fisherman. (2) Finding the suitability of financing should be given to small scale fisherman that Islamic finance. This study uses qualitative research with a phenomenological approach, data analysis focuses on the problem of research, namely the problem of financing small-scale fisherman in Untia village. As for the results of this study, the problems of small-scale fishermen are grouped into four. If the problem is caused by technical factors then the financing models that can be given is Ijara and murabaha. If the problems caused by cultural factors then the financing model that can be given is qardh. Problems caused by natural factors then the financing models that can be given is qardh education and greetings. If the problem is caused by factors Infrastructure provisioning then the financing models that can be given is the policy through sukuk.